Molecular Cloning Using In Vivo DNA Assembly - Arroyo-Urea, Sandra; Watson, Jake; García-Nafría, Javier (DNA Manipulation and Analysis)
Here we describe the in vivo DNA assembly approach, where molecular cloning procedures are performed using an E. coli recA-independent recombination pathway, which assembles linear fragments of DNA with short homologous termini. This pathway is present in all standard laboratory E. coli strains and, by bypassing the need for in vitro DNA assembly, allows simplified molecular cloning to be performed without the plasmid instability issues associated with specialized recombination-cloning bacterial strains. The methodology requires specific primer design and can perform all standard plasmid modifications (insertions, deletions, mutagenesis, and sub-cloning) in a rapid, simple, and cost-efficient manner, as it does not require commercial kits or specialized bacterial strains. Additionally, this approach can be used to perform complex procedures such as multiple modifications to a plasmid, as up to 6 linear fragments can be assembled in vivo by this recombination pathway. Procedures generally require less than 3 h, involving PCR amplification, DpnI digestion of template DNA, and transformation, upon which circular plasmids are assembled. In this chapter we describe the requirements, procedure, and potential pitfalls when using this technique, as well as protocol variations to overcome the most common issues.

Spin-electric coupling in lead halide perovskites - Volosniev, Artem; Shiva Kumar, Abhishek; Lorenc, Dusan; Ashourishokri, Younes; Zhumekenov, Ayan A.; Bakr, Osman M.; Lemeshko, Mikhail; Alpichshev, Zhanybek (Physical Review Letters)
Lead halide perovskites enjoy a number of remarkable optoelectronic properties. To explain their origin, it is necessary to study how electromagnetic fields interact with these systems. We address this problem here by studying two classical quantities: Faraday rotation and the complex refractive index in a paradigmatic perovskite CH3NH3PbBr3 in a broad wavelength range. We find that the minimal coupling of electromagnetic fields to the k⋅p Hamiltonian is insufficient to describe the observed data even on the qualitative level. To amend this, we demonstrate that there exists a relevant atomic-level coupling between electromagnetic fields and the spin degree of freedom. This spin-electric coupling allows for quantitative description of a number of previous as well as present experimental data. In particular, we use it here to show that the Faraday effect in lead halide perovskites is dominated by the Zeeman splitting of the energy levels and has a substantial beyond-Becquerel contribution. Finally, we present general symmetry-based phenomenological arguments that in the low-energy limit our effective model includes all basis coupling terms to the electromagnetic field in the linear order.
Keywords: General Physics and Astronomy

Effective model for studying optical properties of lead halide perovskites - Volosniev, Artem; Shiva Kumar, Abhishek; Lorenc, Dusan; Ashourishokri, Younes; Zhumekenov, Ayan; Bakr, Osman M.; Lemeshko, Mikhail; Alpichshev, Zhanybek (Physical Review B)
We use general symmetry-based arguments to construct an effective model suitable for studying optical properties of lead halide perovskites. To build the model, we identify an atomic-level interaction between electromagnetic fields and the spin degree of freedom that should be added to a minimally coupled k⋅p Hamiltonian. As a first application, we study two basic optical characteristics of the material: the Verdet constant and the refractive index. Beyond these linear characteristics of the material, the model is suitable for calculating nonlinear effects such as the third-order optical susceptibility. Analysis of this quantity shows that the geometrical properties of the spin-electric term imply isotropic optical response of the system, and that optical anisotropy of lead halide perovskites is a manifestation of hopping of charge carriers. To illustrate this, we discuss third-harmonic generation.

Synchronization in collectively moving active matter - Riedl, Michael
Most motions of many-body systems at any scale in nature with sufficient degrees of freedom tend to be chaotic; reaching from the orbital motion of planets, the air currents in our atmosphere, down to the water flowing through our pipelines or the movement of a population of bacteria. To the observer it is therefore intriguing when a moving collective exhibits order. Collective motion of flocks of birds, schools of fish or swarms of self-propelled particles or robots have been studied extensively over the past decades but the mechanisms involved in the transition from chaos to order remain unclear. Here, the interactions, that in most systems give rise to chaos, sustain order. In this thesis we investigate mechanisms that preserve, destabilize or lead to the ordered state. We show that endothelial cells migrating in circular confinements transition to a collective rotating state and concomitantly synchronize the frequencies of nucleating actin waves within individual cells. Consequently, the frequency dependent cell migration speed uniformizes across the population. Complementary to the WAVE dependent nucleation of traveling actin waves, we show that in leukocytes the actin polymerization depending on WASp generates pushing forces locally at stationary patches. Next, in pipe flows, we study methods to disrupt the self–sustaining cycle of turbulence and therefore relaminarize the flow. While we find in pulsating flow conditions that turbulence emerges through a helical instability during the decelerating phase. Finally, we show quantitatively in brain slices of mice that wild-type control neurons can compensate the migratory deficits of a genetically modified neuronal sub–population in the developing cortex.

Ergodicity breaking in disordered and kinetically constrained quantum many-body systems - Brighi, Pietro
Nonergodic systems, whose out-of-equilibrium dynamics fail to thermalize, provide a fascinating research direction both for fundamental reasons and for application in state of the art quantum devices. Going beyond the description of statistical mechanics, ergodicity breaking yields a new paradigm in quantum many-body physics, introducing novel phases of matter with no counterpart at equilibrium. In this Thesis, we address different open questions in the field, focusing on disorder-induced many-body localization (MBL) and on weak ergodicity breaking in kinetically constrained models. In particular, we contribute to the debate about transport in kinetically constrained models, studying the effect of $U(1)$ conservation and inversion-symmetry breaking in a family of quantum East models. Using tensor network techniques, we analyze the dynamics of large MBL systems beyond the limit of exact numerical methods. In this setting, we approach the debated topic of the coexistence of localized and thermal eigenstates separated by energy thresholds known as many-body mobility edges. Inspired by recent experiments, our work further investigates the localization of a small bath induced by the coupling to a large localized chain, the so-called MBL proximity effect. In the first Chapter, we introduce a family of particle-conserving kinetically constrained models, inspired by the quantum East model. The system we study features strong inversion-symmetry breaking, due to the nature of the correlated hopping. We show that these models host so-called quantum Hilbert space fragmentation, consisting of disconnected subsectors in an entangled basis, and further provide an analytical description of this phenomenon. We further probe its effect on dynamics of simple product states, showing revivals in fidelity and local observalbes. The study of dynamics within the largest subsector reveals an anomalous transient superdiffusive behavior crossing over to slow logarithmic dynamics at later times. This work suggests that particle conserving constrained models with inversion-symmetry breaking realize new universality classes of dynamics and invite their further theoretical and experimental studies. Next, we use kinetic constraints and disorder to design a model with many-body mobility edges in particle density. This feature allows to study the dynamics of localized and thermal states in large systems beyond the limitations of previous studies. The time-evolution shows typical signatures of localization at small densities, replaced by thermal behavior at larger densities. Our results provide evidence in favor of the stability of many-body mobility edges, which was recently challenged by a theoretical argument. To support our findings, we probe the mechanism proposed as a cause of delocalization in many-body localized systems with mobility edges suggesting its ineffectiveness in the model studied. In the last Chapter of this Thesis, we address the topic of many-body localization proximity effect. We study a model inspired by recent experiments, featuring Anderson localized coupled to a small bath of free hard-core bosons. The interaction among the two particle species results in non-trivial dynamics, which we probe using tensor network techniques. Our simulations show convincing evidence of many-body localization proximity effect when the bath is composed by a single free particle and interactions are strong. We furthter observe an anomalous entanglement dynamics, which we explain through a phenomenological theory. Finally, we extract highly excited eigenstates of large systems, providing supplementary evidence in favor of our findings.

Fast and scalable channels in Kotlin Coroutines - Koval, Nikita; Alistarh, Dan-Adrian; Elizarov, Roman (Proceedings of the ACM SIGPLAN Symposium on Principles and Practice of Parallel Programming)
Asynchronous programming has gained significant popularity over the last decade: support for this programming pattern is available in many popular languages via libraries and native language implementations, typically in the form of coroutines or the async/await construct. Instead of programming via shared memory, this concept assumes implicit synchronization through message passing. The key data structure enabling such communication is the rendezvous channel. Roughly, a rendezvous channel is a blocking queue of size zero, so both send(e) and receive() operations wait for each other, performing a rendezvous when they meet. To optimize the message passing pattern, channels are usually equipped with a fixed-size buffer, so sends do not suspend and put elements into the buffer until its capacity is exceeded. This primitive is known as a buffered channel. This paper presents a fast and scalable algorithm for both rendezvous and buffered channels. Similarly to modern queues, our solution is based on an infinite array with two positional counters for send(e) and receive() operations, leveraging the unconditional Fetch-And-Add instruction to update them. Yet, the algorithm requires non-trivial modifications of this classic pattern, in order to support the full channel semantics, such as buffering and cancellation of waiting requests. We compare the performance of our solution to that of the Kotlin implementation, as well as against other academic proposals, showing up to 9.8× speedup. To showcase its expressiveness and performance, we also integrated the proposed algorithm into the standard Kotlin Coroutines library, replacing the previous channel implementations.

Unexpected scaling in path copying trees - Aksenov, Vitaly; Brown, Trevor A; Fedorov, Alexander; Kokorin, Ilya (Proceedings of the ACM SIGPLAN Symposium on Principles and Practice of Parallel Programming)
Although a wide variety of handcrafted concurrent data structures have been proposed, there is considerable interest in universal approaches (Universal Constructions or UCs) for building concurrent data structures. UCs (semi-)automatically convert a sequential data structure into a concurrent one. The simplest approach uses locks [3, 6] that protect a sequential data structure and allow only one process to access it at a time. However, the resulting data structure is blocking. Most work on UCs instead focuses on obtaining non-blocking progress guarantees such as obstruction-freedom, lock-freedom or wait-freedom. Many non-blocking UCs have appeared. Key examples include the seminal wait-free UC [2] by Herlihy, a NUMA-aware UC [10] by Yi et al., and an efficient UC for large objects [1] by Fatourou et al.

Highly adaptive nature of group 15 tris(quinolyl) ligands─studies with coinage metals - García-Romero, Álvaro; Waters, Jessica E.; Jethwa, Rajesh B; Bond, Andrew D.; Colebatch, Annie L.; García-Rodríguez, Raúl; Wright, Dominic S. (Inorganic Chemistry)
The substitution of heavier, more metallic atoms into classical organic ligand frameworks provides an important strategy for tuning ligand properties, such as ligand bite and donor character, and is the basis for the emerging area of main-group supramolecular chemistry. In this paper, we explore two new ligands [E(2-Me-8-qy)3] [E = Sb (1), Bi (2); qy = quinolyl], allowing a fundamental comparison of their coordination behavior with classical tris(2-pyridyl) ligands of the type [E′(2-py)3] (E = a range of bridgehead atoms and groups, py = pyridyl). A range of new coordination modes to Cu+, Ag+, and Au+ is seen for 1 and 2, in the absence of steric constraints at the bridgehead and with their more remote N-donor atoms. A particular feature is the adaptive nature of these new ligands, with the ability to adjust coordination mode in response to the hard–soft character of coordinated metal ions, influenced also by the character of the bridgehead atom (Sb or Bi). These features can be seen in a comparison between [Cu2{Sb(2-Me-8-qy)3}2](PF6)2 (1·CuPF6) and [Cu{Bi(2-Me-8-qy)3}](PF6) (2·CuPF6), the first containing a dimeric cation in which 1 adopts an unprecedented intramolecular N,N,Sb-coordination mode while in the second, 2 adopts an unusual N,N,(π-)C coordination mode. In contrast, the previously reported analogous ligands [E(6-Me-2-py)3] (E = Sb, Bi; 2-py = 2-pyridyl) show a tris-chelating mode in their complexes with CuPF6, which is typical for the extensive tris(2-pyridyl) family with a range of metals. The greater polarity of the Bi–C bond in 2 results in ligand transfer reactions with Au(I). Although this reactivity is not in itself unusual, the characterization of several products by single-crystal X-ray diffraction provides snapshots of the ligand transfer reaction involved, with one of the products (the bimetallic complex [(BiCl){ClAu2(2-Me-8-qy)3}] (8)) containing a Au2Bi core in which the shortest Au → Bi donor–acceptor bond to date is observed.

PCYT2-regulated lipid biosynthesis is critical to muscle health and ageing - Cikes, Domagoj; Elsayad, Kareem; Sezgin, Erdinc; Koitai, Erika; Ferenc, Torma; Orthofer, Michael; Yarwood, Rebecca; Heinz, Leonhard X.; Sedlyarov, Vitaly; Darwish-Miranda, Nasser; Taylor, Adrian; Grapentine, Sophie; et al. (Nature Metabolism)
Muscle degeneration is the most prevalent cause for frailty and dependency in inherited diseases and ageing. Elucidation of pathophysiological mechanisms, as well as effective treatments for muscle diseases, represents an important goal in improving human health. Here, we show that the lipid synthesis enzyme phosphatidylethanolamine cytidyltransferase (PCYT2/ECT) is critical to muscle health. Human deficiency in PCYT2 causes a severe disease with failure to thrive and progressive weakness. pcyt2-mutant zebrafish and muscle-specific Pcyt2-knockout mice recapitulate the participant phenotypes, with failure to thrive, progressive muscle weakness and accelerated ageing. Mechanistically, muscle Pcyt2 deficiency affects cellular bioenergetics and membrane lipid bilayer structure and stability. PCYT2 activity declines in ageing muscles of mice and humans, and adeno-associated virus-based delivery of PCYT2 ameliorates muscle weakness in Pcyt2-knockout and old mice, offering a therapy for individuals with a rare disease and muscle ageing. Thus, PCYT2 plays a fundamental and conserved role in vertebrate muscle health, linking PCYT2 and PCYT2-synthesized lipids to severe muscle dystrophy and ageing.
Keywords: Cell Biology; Physiology (medical); Endocrinology; Diabetes and Metabolism; Internal Medicine

The patterned assembly and stepwise Vps4-mediated disassembly of composite ESCRT-III polymers drives archaeal cell division - Hurtig, Fredrik; Burgers, Thomas C.Q.; Cezanne, Alice; Jiang, Xiuyun; Mol, Frank N.; Traparić, Jovan; Pulschen, Andre Arashiro; Nierhaus, Tim; Tarrason-Risa, Gabriel; Harker-Kirschneck, Lena; Löwe, Jan; Šarić, Anđela; et al. (Science Advances)
ESCRT-III family proteins form composite polymers that deform and cut membrane tubes in the context of a wide range of cell biological processes across the tree of life. In reconstituted systems, sequential changes in the composition of ESCRT-III polymers induced by the AAA–adenosine triphosphatase Vps4 have been shown to remodel membranes. However, it is not known how composite ESCRT-III polymers are organized and remodeled in space and time in a cellular context. Taking advantage of the relative simplicity of the ESCRT-III–dependent division system in Sulfolobus acidocaldarius, one of the closest experimentally tractable prokaryotic relatives of eukaryotes, we use super-resolution microscopy, electron microscopy, and computational modeling to show how CdvB/CdvB1/CdvB2 proteins form a precisely patterned composite ESCRT-III division ring, which undergoes stepwise Vps4-dependent disassembly and contracts to cut cells into two. These observations lead us to suggest sequential changes in a patterned composite polymer as a general mechanism of ESCRT-III–dependent membrane remodeling.

From the 'black box' to 'domino effect' mechanism: What have we learned from the structures of respiratory complex I - Sazanov, Leonid A (The Biochemical Journal)
My group and myself have studied respiratory complex I for almost 30 years, starting in 1994 when it was known as a L-shaped giant ‘black box' of bioenergetics. First breakthrough was the X-ray structure of the peripheral arm, followed by structures of the membrane arm and finally the entire complex from Thermus thermophilus. The developments in cryo-EM technology allowed us to solve the first complete structure of the twice larger, ∼1 MDa mammalian enzyme in 2016. However, the mechanism coupling, over large distances, the transfer of two electrons to pumping of four protons across the membrane remained an enigma. Recently we have solved high-resolution structures of mammalian and bacterial complex I under a range of redox conditions, including catalytic turnover. This allowed us to propose a robust and universal mechanism for complex I and related protein families. Redox reactions initially drive conformational changes around the quinone cavity and a long-distance transfer of substrate protons. These set up a stage for a series of electrostatically driven proton transfers along the membrane arm (‘domino effect'), eventually resulting in proton expulsion from the distal antiporter-like subunit. The mechanism radically differs from previous suggestions, however, it naturally explains all the unusual structural features of complex I. In this review I discuss the state of knowledge on complex I, including the current most controversial issues.

Using AlphaFold to predict the impact of single mutations on protein stability and function - Pak, Marina A.; Markhieva, Karina A.; Novikova, Mariia S.; Petrov, Dmitry S.; Vorobyev, Ilya S.; Maksimova, Ekaterina; Kondrashov, Fyodor; Ivankov, Dmitry N. (PLoS ONE)
AlphaFold changed the field of structural biology by achieving three-dimensional (3D) structure prediction from protein sequence at experimental quality. The astounding success even led to claims that the protein folding problem is “solved”. However, protein folding problem is more than just structure prediction from sequence. Presently, it is unknown if the AlphaFold-triggered revolution could help to solve other problems related to protein folding. Here we assay the ability of AlphaFold to predict the impact of single mutations on protein stability (ΔΔG) and function. To study the question we extracted the pLDDT and <pLDDT> metrics from AlphaFold predictions before and after single mutation in a protein and correlated the predicted change with the experimentally known ΔΔG values. Additionally, we correlated the same AlphaFold pLDDT metrics with the impact of a single mutation on structure using a large scale dataset of single mutations in GFP with the experimentally assayed levels of fluorescence. We found a very weak or no correlation between AlphaFold output metrics and change of protein stability or fluorescence. Our results imply that AlphaFold may not be immediately applied to other problems or applications in protein folding.

Validation of a stereological method for estimating particle size and density from 2D projections with high accuracy - Rothman, Jason Seth; Borges Merjane, Carolina; Holderith, Noemi; Jonas, Peter M; Angus Silver, R. (PLoS ONE)
Stereological methods for estimating the 3D particle size and density from 2D projections are essential to many research fields. These methods are, however, prone to errors arising from undetected particle profiles due to sectioning and limited resolution, known as ‘lost caps’. A potential solution developed by Keiding, Jensen, and Ranek in 1972, which we refer to as the Keiding model, accounts for lost caps by quantifying the smallest detectable profile in terms of its limiting ‘cap angle’ (ϕ), a size-independent measure of a particle’s distance from the section surface. However, this simple solution has not been widely adopted nor tested. Rather, model-independent design-based stereological methods, which do not explicitly account for lost caps, have come to the fore. Here, we provide the first experimental validation of the Keiding model by comparing the size and density of particles estimated from 2D projections with direct measurement from 3D EM reconstructions of the same tissue. We applied the Keiding model to estimate the size and density of somata, nuclei and vesicles in the cerebellum of mice and rats, where high packing density can be problematic for design-based methods. Our analysis reveals a Gaussian distribution for ϕ rather than a single value. Nevertheless, curve fits of the Keiding model to the 2D diameter distribution accurately estimate the mean ϕ and 3D diameter distribution. While systematic testing using simulations revealed an upper limit to determining ϕ, our analysis shows that estimated ϕ can be used to determine the 3D particle density from the 2D density under a wide range of conditions, and this method is potentially more accurate than minimum-size-based lost-cap corrections and disector methods. Our results show the Keiding model provides an efficient means of accurately estimating the size and density of particles from 2D projections even under conditions of a high density.

Dynamic maintenance of monotone dynamic programs and applications - Henzinger, Monika H; Neumann, Stefan; Räcke, Harald; Schmid, Stefan (40th International Symposium on Theoretical Aspects of Computer Science)
Dynamic programming (DP) is one of the fundamental paradigms in algorithm design. However, many DP algorithms have to fill in large DP tables, represented by two-dimensional arrays, which causes at least quadratic running times and space usages. This has led to the development of improved algorithms for special cases when the DPs satisfy additional properties like, e.g., the Monge property or total monotonicity. In this paper, we consider a new condition which assumes (among some other technical assumptions) that the rows of the DP table are monotone. Under this assumption, we introduce a novel data structure for computing (1 + ϵ)-approximate DP solutions in near-linear time and space in the static setting, and with polylogarithmic update times when the DP entries change dynamically. To the best of our knowledge, our new condition is incomparable to previous conditions and is the first which allows to derive dynamic algorithms based on existing DPs. Instead of using two-dimensional arrays to store the DP tables, we store the rows of the DP tables using monotone piecewise constant functions. This allows us to store length-n DP table rows with entries in [0, W] using only polylog(n, W) bits, and to perform operations, such as (min, +)-convolution or rounding, on these functions in polylogarithmic time. We further present several applications of our data structure. For bicriteria versions of k-balanced graph partitioning and simultaneous source location, we obtain the first dynamic algorithms with subpolynomial update times, as well as the first static algorithms using only near-linear time and space. Additionally, we obtain the currently fastest algorithm for fully dynamic knapsack.

Functional central limit theorems for Wigner matrices - Cipolloni, Giorgio; Erdös, László; Schröder, Dominik J (Annals of Applied Probability)
We consider the fluctuations of regular functions f of a Wigner matrix W viewed as an entire matrix f (W). Going beyond the well-studied tracial mode, Trf (W), which is equivalent to the customary linear statistics of eigenvalues, we show that Trf (W)A is asymptotically normal for any nontrivial bounded deterministic matrix A. We identify three different and asymptotically independent modes of this fluctuation, corresponding to the tracial part, the traceless diagonal part and the off-diagonal part of f (W) in the entire mesoscopic regime, where we find that the off-diagonal modes fluctuate on a much smaller scale than the tracial mode. As a main motivation to study CLT in such generality on small mesoscopic scales, we determine the fluctuations in the eigenstate thermalization hypothesis (Phys. Rev. A 43 (1991) 2046–2049), that is, prove that the eigenfunction overlaps with any deterministic matrix are asymptotically Gaussian after a small spectral averaging. Finally, in the macroscopic regime our result also generalizes (Zh. Mat. Fiz. Anal. Geom. 9 (2013) 536–581, 611, 615) to complex W and to all crossover ensembles in between. The main technical inputs are the recent multiresolvent local laws with traceless deterministic matrices from the companion paper (Comm. Math. Phys. 388 (2021) 1005–1048).

Statistical modeling of adaptive neural networks explains co-existence of avalanches and oscillations in resting human brain - Lombardi, Fabrizio; Pepic, Selver; Shriki, Oren; Tkačik, Gašper; De Martino, Daniele (Nature Computational Science)
Neurons in the brain are wired into adaptive networks that exhibit collective dynamics as diverse as scale-specific oscillations and scale-free neuronal avalanches. Although existing models account for oscillations and avalanches separately, they typically do not explain both phenomena, are too complex to analyze analytically or intractable to infer from data rigorously. Here we propose a feedback-driven Ising-like class of neural networks that captures avalanches and oscillations simultaneously and quantitatively. In the simplest yet fully microscopic model version, we can analytically compute the phase diagram and make direct contact with human brain resting-state activity recordings via tractable inference of the model’s two essential parameters. The inferred model quantitatively captures the dynamics over a broad range of scales, from single sensor oscillations to collective behaviors of extreme events and neuronal avalanches. Importantly, the inferred parameters indicate that the co-existence of scale-specific (oscillations) and scale-free (avalanches) dynamics occurs close to a non-equilibrium critical point at the onset of self-sustained oscillations.

The reach of subsets of manifolds - Boissonnat, Jean Daniel; Wintraecken, Mathijs (Journal of Applied and Computational Topology)
Kleinjohann (Archiv der Mathematik 35(1):574–582, 1980; Mathematische Zeitschrift 176(3), 327–344, 1981) and Bangert (Archiv der Mathematik 38(1):54–57, 1982) extended the reach rch(S) from subsets S of Euclidean space to the reach rchM(S) of subsets S of Riemannian manifolds M, where M is smooth (we’ll assume at least C3). Bangert showed that sets of positive reach in Euclidean space and Riemannian manifolds are very similar. In this paper we introduce a slight variant of Kleinjohann’s and Bangert’s extension and quantify the similarity between sets of positive reach in Euclidean space and Riemannian manifolds in a new way: Given p∈M and q∈S, we bound the local feature size (a local version of the reach) of its lifting to the tangent space via the inverse exponential map (exp−1p(S)) at q, assuming that rchM(S) and the geodesic distance dM(p,q) are bounded. These bounds are motivated by the importance of the reach and local feature size to manifold learning, topological inference, and triangulating manifolds and the fact that intrinsic approaches circumvent the curse of dimensionality.

Discrete yamabe problem for polyhedral surfaces - Kourimska, Hana (Discrete and Computational Geometry)
We study a new discretization of the Gaussian curvature for polyhedral surfaces. This discrete Gaussian curvature is defined on each conical singularity of a polyhedral surface as the quotient of the angle defect and the area of the Voronoi cell corresponding to the singularity. We divide polyhedral surfaces into discrete conformal classes using a generalization of discrete conformal equivalence pioneered by Feng Luo. We subsequently show that, in every discrete conformal class, there exists a polyhedral surface with constant discrete Gaussian curvature. We also provide explicit examples to demonstrate that this surface is in general not unique.

Behavioural defences against parasites across host social structures - Stockmaier, Sebastian; Ulrich, Yuko; Albery, Gregory F.; Cremer, Sylvia; Lopes, Patricia C. (Functional Ecology)
Animals exhibit a variety of behavioural defences against socially transmitted parasites. These defences evolved to increase host fitness by avoiding, resisting or tolerating infection. Because they can occur in both infected individuals and their uninfected social partners, these defences often have important consequences for the social group. Here, we discuss the evolution and ecology of anti-parasite behavioural defences across a taxonomically wide social spectrum, considering colonial groups, stable groups, transitional groups and solitary animals. We discuss avoidance, resistance and tolerance behaviours across these social group structures, identifying how social complexity, group composition and interdependent social relationships may contribute to the expression and evolution of behavioural strategies. Finally, we outline avenues for further investigation such as approaches to quantify group-level responses, and the connection of the physiological and behavioural response to parasites in different social contexts.

Modulatory mechanisms of TARP γ8-selective AMPA receptor therapeutics - Zhang, Danyang; Lape, Remigijus; Shaikh, Saher A.; Kohegyi, Bianka K.; Watson, Jake; Cais, Ondrej; Nakagawa, Terunaga; Greger, Ingo H. (Nature Communications)
AMPA glutamate receptors (AMPARs) mediate excitatory neurotransmission throughout the brain. Their signalling is uniquely diversified by brain region-specific auxiliary subunits, providing an opportunity for the development of selective therapeutics. AMPARs associated with TARP γ8 are enriched in the hippocampus, and are targets of emerging anti-epileptic drugs. To understand their therapeutic activity, we determined cryo-EM structures of the GluA1/2-γ8 receptor associated with three potent, chemically diverse ligands. We find that despite sharing a lipid-exposed and water-accessible binding pocket, drug action is differentially affected by binding-site mutants. Together with patch-clamp recordings and MD simulations we also demonstrate that ligand-triggered reorganisation of the AMPAR-TARP interface contributes to modulation. Unexpectedly, one ligand (JNJ-61432059) acts bifunctionally, negatively affecting GluA1 but exerting positive modulatory action on GluA2-containing AMPARs, in a TARP stoichiometry-dependent manner. These results further illuminate the action of TARPs, demonstrate the sensitive balance between positive and negative modulatory action, and provide a mechanistic platform for development of both positive and negative selective AMPAR modulators.